a Aplikasi Kaidah Al-hukmu Yaduru Ma Illatihi di Era Pandemi dan Kebijakan Publik Syariah - Assiddiq, Mahfuz; Nazhir, Firman; Musyahid, Achmad; Kuba, Imran Anwar (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study examines the role of the usul al-fiqh maxim al-hukmu yaduru maa illatihi wujudan wa adaman (a legal ruling revolves with its effective cause in both its existence and nonexistence) as a foundation for the flexibility of Islamic law in responding to contemporary social dynamics. Employing a qualitative library research method, the study analyzes the application of this maxim in both classical cases (such as the prohibition of khamr and the obligation of zakat) and contemporary contexts (including the suspension of Friday prayers and the formulation of Sharia-based policies during the COVID-19 pandemic). The findings indicate that this maxim effectively sustains the relevance of Islamic law by ensuring its conformity with the Maqasid al-Shariah, particularly in safeguarding life (hifz al-nafs) and promoting the public interest (al-maslahah al-ammah). These findings underscore the urgency of applying rational Sharia legal maxims as a foundational basis for the development of positive law oriented toward Islamic values.